2017
DOI: 10.1182/blood-2017-03-770180
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomes in platelets protect the messenger

Abstract: risk of tumor necrosis and toxicity resulting from virus reactivation.7 Second, autologous cytotoxic T cells expanded against EBV antigens have been tested, but the very frequent expression of programmed death ligand 1 (PDL1) and immunosuppressive cytokines by NK/T lymphoma cells could inhibit T-cell cytotoxicity. 8,9 Indeed, in most cases, an immune deficiency is not observed in patients with NK/T-cell lymphoma, strongly suggesting that tumor cells have developed strategies to escape the strong immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
10
2
Order By: Relevance
“…As platelets are anucleate, with a limited translational capacity, this is perhaps unsurprising and could be explained by protein degradation as a result of basal cellular processes and the release of proteins, perhaps encapsulated within platelet microvesicles. 7,26–29 While our data show very clearly that there is a large general loss of proteins, this does not mean that individual proteins are not more subtly regulated. Platelets have the capacity to replenish their protein levels through endocytosis via the open canalicular system, as well as through limited protein synthesis.…”
Section: Discussioncontrasting
confidence: 52%
“…As platelets are anucleate, with a limited translational capacity, this is perhaps unsurprising and could be explained by protein degradation as a result of basal cellular processes and the release of proteins, perhaps encapsulated within platelet microvesicles. 7,26–29 While our data show very clearly that there is a large general loss of proteins, this does not mean that individual proteins are not more subtly regulated. Platelets have the capacity to replenish their protein levels through endocytosis via the open canalicular system, as well as through limited protein synthesis.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, it can be speculated that there is a certain connection between them. In addition, scholars have found that ribosomes play an important role in the translation of platelet proteins [ 31 ], and platelets can promote the formation of NETs, which in turn promotes the formation of deep vein thrombosis [ 32 ]. This conclusion supports our speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that there is a certain connection between them. In addition, scholars have found that ribosomes play an important role in the translation of platelet proteins [25] , and platelets can promote the formation of NETs, which in turn promotes the formation of deep vein thrombosis [26] . This conclusion supports our speculation.…”
Section: Discussionmentioning
confidence: 99%